Pengaruh Penggunaan Game Edukasi Baamboozle Terhadap Motivasi Belajar PPKn Siswa Kelas IV di SD GMIT Kuanino 1: Penelitian Kuantitatif - Stefania Hale; Roswita Nahak; Kristina Noya Nahak (STKIP Subang, 2026)
This research investigates the effect of using the Baamboozle educational game on the learning motivation of fourth-grade students in Civic Education (PPKn) at GMIT Kuanino 1 Elementary School. This research was motivated by the observation that Civic Education learning is often considered monotonous, which reduces students’ enthusiasm and participation. The method used is a quasi-experimental design with a One Group Pretest-Posttest Design, involving 16 students as the research sample. Data were collected using a learning motivation questionnaire and analyzed with validity and reliability tests, normality and homogeneity tests, paired sample t-tests, and N-Gain analysis. The results show that the average score of students’ motivation increased from 42.63 in the pretest to 76.31 in the posttest. The N-Gain score of 0.58 was categorized as moderate, and the paired t-test showed a significance value of 0.000 < 0.05. Thus, the use of Baamboozle as a digital learning medium has a significant positive impact on improving students’ learning motivation in Civic Education.Keywords: Educational Game, Baamboozle, Learning Motivation